Pragmatic Study of Appeal in Speech Etiquette (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Forms of address play a central role in the structure of speech etiquette, functioning as a primary means of establishing and regulating verbal contact between interlocutors. Almost all situations of speech communication begin with an address, which reflects social relations, communicative roles, and the speaker’s attitude toward the addressee. This article examines the concept of address within the framework of speech etiquette and analyzes its role in verbal interaction. The study highlights the standardized and nationally specific nature of address formulas and their dependence on social, biological, and situational factors, including age, gender, social status, communicative distance, and the level of communication (social-role, business, or intimate-personal). Particular attention is paid to the role of address formulas in maintaining politeness, ensuring successful interaction, and achieving mutual understanding in both interpersonal and intercultural communication. The article concludes that the appropriate choice of forms of address is a crucial condition for effective speech interaction and harmonious communicative behavior.